ﻲﻓ ﺪﯿﻤﺴﺘﻟاو ةﺪﻤﺳﻷا ﻞﻛﺎﺸﻣ ﺮﺼﻣ - Kaoud, Alsaid (2019)
As part of the seminar held by the International Food Policy Research Institute (IFPRI) under the title of " Fertilizer policy in Egypt and options for improvements".